THE ROLE OF ENGLISH FOR SPECIFIC PURPOSES (ESP) IN TECHNICAL COLLEGE EDUCATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
In the context of globalization and rapid technological development, English has become an essential tool for professional communication in technical fields. Technical college students are increasingly required to use English in their future workplaces, particularly when dealing with technical documentation, international standards, and professional communication. This article examines the role of English for Specific Purposes (ESP) in technical college education.